Analysing Modality in Nairalanders’ Discourse on the Non-Passage of the Gender Equality Bill in Nigeria - Adetutu Aragbuwa (The Journal of Studies in Language, Culture and Society)
The successive rebuttal of the Gender and Equality Opportunity Bill (henceforth, GEO Bill) by members of the upper chamber of Nigeria’s legislature has become a discourse object of scholarly enquiry in (non)Nigerian academia. Scholars across disciplines have engaged this pertinent issue using diverse theoretical perspectives. However, scant (or no) attention has been accorded the rejection narratives in linguistic scholarship; hence, the justification for this study. Situated within corpus-assisted critical discourse studies, the study explores the modal resources in Nairalanders’ discourse on the Nigerian Senate’s rejection of the GEO Bill in 2016 and 2021, with a view to critically analysing Nairalanders’ attitudes to the Bill and its rejection as well as predominant ideologies embedded in the discourse. The data for the study consist of Nairalanders’ discourse corpora on the non-passage of the Bill in 2016 and 2021 retrieved from www.nairaland.com. A Keyword-in-Context (KWIC) and collocation analysis of the modal resources found in the corpus were also conducted using AntConc corpus analysis tool. The results reveal that Nairalanders use epistemic and deontic modal resources to dominantly express their two-pronged attitude to the GEO Bill rejection: negativism towards the Bill and positivism to its non-passage. These modal choices tacitly serve ethnic, gender and religious ideological biases that culminate in Nairalanders’ resistive engagement towards the Bill. By implication, the feasibility of gender equality in Nigeria must transcend legal measures; culture re-evaluation and national re-orientation on gender equality for sustainable development must be prioritised.